(untitled) (Applied Biological Research, 2024)
Aedes aegypti (A. aegypti) is responsible for higher rate of dengue, yellow fever and chikungunya in tropical and subtropical areas including India. We have examined the presence of bioactive compounds and larvicidal capability of Parthenium hysterophorus (P. hysterophorus) arial part extracts in the solvents of acetone, methanol and hexane against A. aegypti. Fully fed larva were collected from different residential areas of Gorakhpur and identified as A. aegypti larvae. Four aliquots 250, 500, 750 and 1000, mg/L used for 50% to 95% mortality in 24, 48, 72 and 96 hours (h). Phytochemical analysis revealed that methanol extract had maximum rich in saponin, flavonoid, terpenoid, alkaloid and phenols followed by acetone. But, hexane extracts showed only terpenoid and alkaloid activity. The hexane solvent extract showed the LC50 and LC90 were 1920.05, 1496.72, 979.83, 337.84 and 18883.78, 14213.81, 16754.35 and 1246.1 4, mg/L in 24 to 96 h, respectively. Acetone extracts also showed similar values. However, the methanolic extracts had the LC50 and LC90 as 1351.14, 1029,62, 657.77, 226.29 and 5618.12, 5995.96, 2860.23, 804.75. mg/L from 24-96 h. Our study showed that arial part of P. hysterophorus exhibited maximum toxicity in methanol solvent followed by acetone and hexane against A. aegypti larvae.